2017
DOI: 10.1130/ges01506.1
|View full text |Cite
|
Sign up to set email alerts
|

Controls on hydrothermal fluid flow in caldera-hosted settings: Evidence from Lake City caldera, USA

Abstract: Silicic caldera volcanoes are often associated with hydrothermal systems economically important for electricity generation and localization of ore deposits. Despite their potential importance, the poor exposure that is typical in caldera settings has limited the number of detailed studies of the relationship between caldera structures and fluid flow. We use field mapping, outcrop scale scanline transects, and petrographic analyses to characterize fault rocks, alteration, and veins in the well-exposed 22.9 Ma L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 117 publications
3
11
0
Order By: Relevance
“…In March 2008, field observers reported that 70-80 % of the thermal ring displayed fumarolic activity [Staudacher 2010], so that the thermal anomaly seems linked to hydrothermal fluid circulation in the caldera. This is consistent with models detailed by Stix et al [2003] and 4D mapping of caldera collapse at Piton de la Fournaise Derrien et al, 2020Garden et al [2017, where flow of hydrothermal fluids preferentially follows pre-existing faults. The three other distinct secondary thermal zones ( Figure 4C) seem to be located on the southern ORFs, and close to the location of four older pit-crater events (1953, 1961, 1986 and 2002) at the summit of PdF ( Figure 5E).…”
Section: Active Faults During the Caldera Formation Andsupporting
confidence: 89%
See 1 more Smart Citation
“…In March 2008, field observers reported that 70-80 % of the thermal ring displayed fumarolic activity [Staudacher 2010], so that the thermal anomaly seems linked to hydrothermal fluid circulation in the caldera. This is consistent with models detailed by Stix et al [2003] and 4D mapping of caldera collapse at Piton de la Fournaise Derrien et al, 2020Garden et al [2017, where flow of hydrothermal fluids preferentially follows pre-existing faults. The three other distinct secondary thermal zones ( Figure 4C) seem to be located on the southern ORFs, and close to the location of four older pit-crater events (1953, 1961, 1986 and 2002) at the summit of PdF ( Figure 5E).…”
Section: Active Faults During the Caldera Formation Andsupporting
confidence: 89%
“…The three other distinct secondary thermal zones ( Figure 4C) seem to be located on the southern ORFs, and close to the location of four older pit-crater events (1953, 1961, 1986 and 2002) at the summit of PdF ( Figure 5E). These secondary thermal zones are more spatially diffuse than the main thermal ring, therefore inter-granular fluid flow may happen inside intra-caldera breccia at these locations (a process also evidenced by Garden et al [2017]). A well-developed hydrothermal system is inferred below the summit [e.g.…”
Section: Active Faults During the Caldera Formation Andmentioning
confidence: 97%
“…Magmatic fluids stored in deep‐seated reservoirs beneath caldera systems hold high potential for geothermal exploration and production (e.g., Fulignati et al., 1997; Giordano et al., 2014; Grigsby, 1982), especially in resurgent caldera settings that are often associated with the shallow emplacement of magma and the related development of hydrothermal systems within the caldera deposits (Lipman, 1984; Wohletz & Heiken, 1992). Circulation of geothermal fluids is typically controlled by the secondary permeability of faults connected to caldera and resurgence‐forming processes (e.g., Garden et al., 2017; Giordano et al., 2014). Therefore, faults represent optimal targets for unlocking geothermal fluids (Martí et al., 2008).…”
Section: Introduction and Aims Of The Studymentioning
confidence: 99%
“…The above discussion suggests that inherited discontinuities can be reactivated during the caldera collapse. Considering that at LH and in other caldera collapse settings (e.g., Martí et al, 2008;Giordano et al 2014;Norini et al, 2015Norini et al, , 2019Garden et al 2017;Liotta and WP4 Working Group, 2019;Montanari et al 2017a;Jentsch et al, 2020) caldera structures are considered to bear a potential for favouring the upward migration of hydrothermal fluids, we speculate that these reactivated structures may behave in a similar manner. Besides, the presence/lack of calderarelated structures due to the possible inhibition induced by inherited fault reactivation is a condition that may influence the degree of fracturation and consequently the secondary permeability and fluid flow inside the caldera complex, therefore strongly affecting the geothermal potential.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 90%